Glaucoma detection: the content of optometric eye examinations for a presbyopic patient of African racial descent. Issue 4 (5th December 2008) - Shah, R; Edgar, D F; Spry, P G; Harper, R A; Kotecha, A; Rughani, S; Evans, B J W
Abstract : Aims: Standardised patient (SP) methodology is the gold standard for evaluating clinical practice. We investigated the content of optometric eyecare for an early presbyopic SP of African racial descent, an "at-risk" patient group for primary open-angle glaucoma (POAG). Methods: A trained actor presented unannounced as a 44-year-old patient of African racial descent, complaining of recent near vision difficulties, to 100 community optometrists for an audio-recorded eye examination. The eye examinations were subsequently assessed via a checklist based on evidence-based POAG reviews, clinical guidelines and expert panel opinion. Results: Ninety-five per cent of optometrists carried out optic disc assessment and tonometry, which conforms to the UK College of Optometrists' advice that those patients aged >40 years should receive at least two of the following tests: tonometry, optic disc assessment, visual field testing. Thirty-five per cent of optometrists carried out all of these tests and 6% advised the SP of increased POAG risk in those of African racial descent. Conclusion: SP encounters are an effective measure of optometric clinical practice. As in other healthcare disciplines, there are substantial differences between optometrists in the depth of their clinical investigations, challenging the concept of a "standard sight test". There is a need for continuing professional development (CPD) in glaucoma screening, in which the increased risk of POAG in those of African racial descent should be emphasised.